1973
DOI: 10.1246/bcsj.46.3099
|View full text |Cite
|
Sign up to set email alerts
|

The Solubility of Sulfur in Na2O–SiO2 Melts under Various Oxygen Partial Pressures at 1100 °C, 1250 °C, and 1300 °C

Abstract: The solubility of sulfur in Na2O–SiO2 melts with the Na2O/SiO2 molar ratios of 1/3, 1/2, and 1/1 was investigated by varying the oxygen partial pressure at 1100, 1250, and 1300 °C. The results at 1100 °C are complicated, for the equilibrium state within the gas phase is not established. From the experiments at 1250 and 1300 °C, the following conclusions are reached: (1) When the temperature and the Na2O/SiO2 ratio in the melt are constant, the solubility of sulfur increases with an increase of the total amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1

Year Published

1973
1973
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 10 publications
6
43
1
Order By: Relevance
“…Principally this is a result of changes in SiO 2 content and, as expected based on previous studies [18][19][20][21], sulfate content increases with decreasing SiO 2 content. However, changes in the proportions of the other constituents also arise making it necessary to a consider both glass composition and structure if accurate modelling of sulfate capacity is to be carried out.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Principally this is a result of changes in SiO 2 content and, as expected based on previous studies [18][19][20][21], sulfate content increases with decreasing SiO 2 content. However, changes in the proportions of the other constituents also arise making it necessary to a consider both glass composition and structure if accurate modelling of sulfate capacity is to be carried out.…”
Section: Resultssupporting
confidence: 77%
“…temperatures play a role, since lower melting temperatures can enhance the sulfate capacity and solubility in some oxide melts [18][19][20]. However, other possible explanations also exist and further work is required to explain this behaviour.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the dissolved S content in a basic magma does not change significantly as a function of pressure at lithospheric depths (Wallace and Carmichael, 1992). It has also been shown that at magmatic temperatures, S is present predominantly as sulfide at fo 2 more reduced than the fayalite-magnetite-quartz (FMQ) buffer (e.g., Nagashima and Katsura, 1973;Carrol and Rutherford, 1985). The S 6+ /S tot ratio further correlates positively with fo 2 for sulfur-undersaturated melts.…”
Section: Sulfur Speciation and Oxygen Fugacitymentioning
confidence: 99%